Identification of triterpene from the leaves and bark of kopsia singapurensis Ridl. (SELADA) - Lee, Yean Shan (N/A, 2015)
Identification of triterpene from the leaves and bark of kopsia singapurensis Ridl. (SELADA) by Lee, Yean Shan